THE Effect of the Decision to Exempt from Delay Fines on Carrying Governmental Reforms (Cabinet Resolution No. 7 of 2016) - Rouaa Ali Atiyah (Journal of Legal Sciences, 2024)
The idea of ​​the research is based on finding solutions and proposals for the procedures for exempting the private sector companies from the late fines as an exception to the instructions for implementing government contracts No. (1) for the year 2008 and (2) for the year 2014 and the general conditions for civil engineering contracting in its first and second sections prepared by the relevant departments in the Ministry of Planning and the issued decision From the Council of Ministers No. (7) of 2016 .. to be a guide to be used by public sector institutions such as ministries and all entities not associated with the Ministry and the governorates that are not organized in a region (especially with regard to government contract formations and the investment plan) when the private sector companies are delayed or broken in carrying out the tasks assigned to it according to the agreed time schedule in the contract and to avoid personal jurisprudence. The fine for delay in contracts is characterized by the fact that it is subject to a special legal system, compared to other financial penalties in the field of contracts, compensation and fines, which reveals through scientific practice the legal problems of this financial penalty, especially with the growing contractual method resorted to by the various administrations of the state in order to perform their tasks, which should be in the public interest, with the need to achieve at the same time, not to waste the rights of the contractor with the administration, and to ward off the abuse of the administration in its exercise of the privileges of public authority, which It is embodied - indeed - in the mechanisms of execution of contracts, especially when imposing this sanction, which is not accompanied by the need to prove the damage on the part of the contracting administrative authority to sign it, its full discretion in this regard, and the position of the judiciary towards the exercise of this power, within the framework of a system that mainly takes into account the principles established by the French Council of State in this regard, which constitute the historical source of law, In addition, a comparative study is the best way to understand legal ideas and highlight legal principles at the stage of contract implementation.